2017
DOI: 10.1111/apa.13805
|View full text |Cite
|
Sign up to set email alerts
|

The Global Network Neonatal Cause of Death algorithm for low‐resource settings

Abstract: Aim This study estimated the causes of neonatal death using an algorithm for low-resource areas, where 98% of the world’s neonatal deaths occur. Methods We enrolled women in India, Pakistan, Guatemala, the Democratic Republic of Congo, Kenya and Zambia from 2014–2016 and tracked their delivery and newborn outcomes for up to 28 days. Antenatal care and delivery symptoms were collected using a structured questionnaire, clinical observation and, or, a physical examination. The Global Network Cause of Death algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Howbeit, some of our findings might point to some contributory factors like delayed detection or delayed referral or both. Delayed detection may arise from inadequate antenatal care and lack of routine well baby examination which has also been previously reported from some developing countries13,14; or inability of the healthcare personnel at the initial point of contact of the patients to identify and evaluate for these disorders. Published works from some developing countries4,5,79,13 have also highlighted the latter reason for delayed detection, indicating that it might contribute to most of the delays in definitive diagnosis and treatment; delayed referral is a consequence of delayed detection.…”
Section: Discussionmentioning
confidence: 84%
“…Howbeit, some of our findings might point to some contributory factors like delayed detection or delayed referral or both. Delayed detection may arise from inadequate antenatal care and lack of routine well baby examination which has also been previously reported from some developing countries13,14; or inability of the healthcare personnel at the initial point of contact of the patients to identify and evaluate for these disorders. Published works from some developing countries4,5,79,13 have also highlighted the latter reason for delayed detection, indicating that it might contribute to most of the delays in definitive diagnosis and treatment; delayed referral is a consequence of delayed detection.…”
Section: Discussionmentioning
confidence: 84%
“…In another paper, Garces et al. evaluated the use of the global network neonatal cause of death algorithm in low‐resource settings in six countries and found that it proved to be a reliable tool. Readers may also be interested in the paper by Magnin et al.…”
Section: Global Child Survival Including Wars Catastrophes and Malnmentioning
confidence: 99%
“…Improving care in public health services: the case of maternal and newborn care in India While significant gains have been made over the last two decades, India continues to lag behind many LMIC peers (NITI, 2018) in maternal and newborn health. The main causes of maternal and newborn deaths are potentially manageable through well-functioning obstetric services (Garces et al, 2017;Say et al, 2014). In India, poor quality obstetric care in public health facilities and the difficulties in changing health worker behaviour have been widely recognised (Chaturvedi et al, 2015;Das et al, 2012;Das et al, 2015;Sharma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%